Eugenics, social thought and identity discourses in Brazil:: between “heróis capengas”, “urupês de pau podre” and “manchas loiras” (Revista de História Regional, 2024)
The study aimed to address the eugenic debates and their repercussions in Brazilian social thought and in national and regional identity discourses. In this sense, it dealt with recurrent conceptualizations around emblematic characters of Brazilian literature, such as Monteiro Lobato's “Jeca Tatu” (1882-1948) and Mário de Andrade's “Macunaíma” (1893-1945). In the first part, the relations of eugenics in social thought were discussed, relating elements referring to sanitarianism, hygiene, and national identity construction; in the second part, the intellectual production of identity representation in southern Brazil was addressed in the arguments of Bento Munhoz da Rocha Netto (1905-1973) and Wilson Martins (1921-2010), both writers from Paraná, politicians, university professors, who established a counterpoint to the regionalist theoretical model on Brazilian formation elaborated by Gilberto Freyre (1900-1987). The proposition of this article was, therefore, to uproot the past and bring to debate the appropriations of these productions of eugenic principles, in order to discern the historiographical scope of the identity idealizations treated.
Keywords: Eugenics; Social Thought; Identity Discourses; Paraná; Brazil